2007
DOI: 10.1093/bja/aem160
|View full text |Cite
|
Sign up to set email alerts
|

Superficial or deep cervical plexus block for carotid endarterectomy: a systematic review of complications †

Abstract: Carotid endarterectomy is commonly conducted under regional (deep, superficial, intermediate, or combined) cervical plexus block, but it is not known if complication rates differ. We conducted a systematic review of published papers to assess the complication rate associated with superficial (or intermediate) and deep (or combined deep plus superficial/intermediate). The null hypothesis was that complication rates were equal. Complications of interest were: (1) serious complications related to the placement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
147
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(160 citation statements)
references
References 95 publications
3
147
0
5
Order By: Relevance
“…[18][19][20][21][22][23][24] Several studies have shown that the SCPB not only improves pain control after thyroidectomy and carotid endarterectomy, [18][19][20][21][22][23][24] but it also decreases PONV after thyroidectomy. 18 Nevertheless, we did not find any differences in postoperative opioid consumption between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] Several studies have shown that the SCPB not only improves pain control after thyroidectomy and carotid endarterectomy, [18][19][20][21][22][23][24] but it also decreases PONV after thyroidectomy. 18 Nevertheless, we did not find any differences in postoperative opioid consumption between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…13 In a systematic review comparing superficial to deep cervical block in adults undergoing carotid endarterectomy, more than 2,500 cases of superficial cervical block were reviewed and no serious complications, including respiratory distress secondary to diaphragmatic or vocal cord paralysis, were recorded. 14 In a cadaveric study, Pandit et al examined patterns of injectate spread after different cervical blocks. 15 Methylene blue was injected into the superficial cervical space in four cadavers, just under the investing cervical fascia (superficial cervical block).…”
Section: Discussionmentioning
confidence: 99%
“…Serious complications after carotid endarterectomy [20]; mortality after pulmonary aspiration [24] $60 $100…”
Section: $3mentioning
confidence: 99%